Genetically modulated educational attainment and coronary disease risk - Zeng, L; Ntalla, I; Kessler, T; Kastrati, A; Erdmann, J; Uk Biobank Cardiometabolic Consortium CHD Working Group; Danesh, J; Watkins, H; Samani, NJ; Deloukas, P; Schunkert, H (Oxford University Press, 2019)
Aims Genetic disposition and lifestyle factors are understood as independent components underlying the risk of multiple diseases. In this study, we aim to investigate the interplay between genetics, educational attainment—an important denominator of lifestyle—and coronary artery disease (CAD) risk.